Mammuthus Population Dynamics in Late Pleistocene North America: Divergence, Phylogeography, and Introgression - Enk, Jacob; Devault, Alison; Widga, Christopher; Saunders, Jeffrey; Szpak, Paul; Southon, John; Rouillard, Jean-Marie; Shapiro, Beth; Golding, G. Brian; Zazula, Grant; Froese, Duane; Fisher, Daniel C.; et al. (Frontiers in Ecology and Evolution, 2016)
After evolving in Africa at the close of the Miocene, mammoths (Mammuthus sp.) spread through much of the northern hemisphere, diversifying morphologically as they entered various habitats. Paleontologically, these morphs are conventionally recognized as species. In Pleistocene North America alone, several mammoth species have been recognized, inhabiting environments as different as cold tundra-steppe in the north and the arid grasslands or temperate savanna-parklands of the south. Yet mammoth phylogeographic studies have overwhelmingly focused on permafrost-preserved remains of only one of these species, Mammuthus primigenius (woolly mammoth). Here we challenge this bias by performing a geographically and taxonomically wide survey of mammoth genetic diversity across North America. Using a targeted enrichment technique, we sequenced 67 complete mitochondrial genomes from non-primigenius specimens representing M. columbi (Columbian mammoth), M. jeffersonii (Jeffersonian mammoth), and M. exilis (pygmy mammoth), including specimens from contexts not generally associated with good DNA preservation. While we uncovered clear phylogeographic structure in mammoth matrilines, their phylogeny as recovered from mitochondrial DNA is not compatible with existing systematic interpretations of their paleontological record. Instead, our results strongly suggest that various nominal mammoth species interbred, perhaps extensively. We hypothesize that at least two distinct stages of interbreeding between conventional paleontological species are likely responsible for this pattern – one between Siberian woolly mammoths and resident American populations that introduced woolly mammoth phenotypes to the continent, and another between ecomorphologically distinct populations of woolly and Columbian mammoths in North America south of the ice.